SUPER PRINCIPAL FIBER BUNDLE WITH SUPER ACTION - Farhangdoost, M.R. (Italian Journal of Pure and Applied Mathematics, 2014)
We introduce super action for supermanifolds to devoted to principal fiber bundle with structural generalized Lie groups. We present a product super fiber bundle, also we extend the coordinate bundle in the sense of Steenrod to show that super coordinate bundles are equivalent if and only if their super actions agree.